Handbook of career counseling theory and practice (Palo Alto, California : Davies-Black, 1996)
A landmark work in the professional literature, the Handbook of Career Counseling Theory and Practice collects in one comprehensive volume in-depth presentations of every major current career counseling theory and important application in use by practitioners. It also presents - for the first time in book form - several new distinct theoretical models for career intervention.
Part One. putting career theory into practice -- Part Two. making career counseling theory more useful -- Part Three. innovation in career assessment -- Part Four. innovation in career counseling -- Par Five. closing comments.
Includes bibliographical references and index.
Keywords: CAREER COUNSELING